Analysis of Community Behavior in Banyumas Regency During the 2021 Covid-19 Emergency PPKM Period - Maulidina, Listia Ayu; Tantowi, Ayesha Liz; Lalita, Rif’at Helsa; Khanza A.P, Regita Octovionanda; Hafizha, Aulia; Hafi Manaf, Safwan; Sakti, Bagas Nurbaya; Ramadhani, Amalia Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The COVID-19 pandemic forces the public to follow health protocols to prevent the virus from spreading. Compliance with these protocols is influenced by factors such as education level and gender. This study aims to analyze the relationship between education level and gender with compliance to health protocols in Banyumas Regency during the COVID-19 Emergency Community Activity Restrictions (PPKM in bahasa) period. The research data was sourced from a survey by the Central Bureau of Statistics (BPS in bahasa) on health protocol compliance in Indonesia The study uses a descriptive quantitative method, where data was analyzed to examine the relationship between education, gender, and compliance. The results show a significant difference in compliance between males and females, with females being more compliant. Respondents with higher education levels also showed better compliance than those with lower education levels. This means that education and gender influence people's compliance in following health protocols. This finding is expected to help the government formulate policies to increase public compliance during the pandemic.